Pengaruh Risiko, Brand image dan Norma Subjektif Terhadap Minat Menabung Di PT. Bank Pembangunan Daerah Nusa Tenggara Timur - Rosadalima Perdona Hayon; Maria Bernadethe Mawarni Gelu Wutun (AKSIOMA : Jurnal Manajemen, 2025)
Research objectives to determine the effect of perceived risk on interest in saving at Bank NTT, to determine the influence of brand image on interest in saving at Bank NTT and to determine the influence of subjective norms on interest in saving at Bank NTT. The sample in this study was 100 respondents who saved at Bank NTT. The data collection technique used was a questionnaire. The analysis used is quantitative descriptive analysis using Smart PLS. The results of the descriptive analysis illustrate that the perceived risk variables are (85.3%), brand image (84%), subjective norms (81.65%), and interest in saving (83.9%) are in the very high category. The results of inferential statistical analysis (PLS) show that: The perceived risk variable does not have a significant effect on interest in saving at Bank NTT, while the brand image and subjective norm variables have a significant effect on interest in saving at Bank NTT. The value of the coefficient of determination R2for the variable interest in saving is 0.816, the remaining 18.4% is influenced by variables other than the variables in the research.